Profile of the Anti-inflammatory Mediator Interleukin-10 (IL-10) in Patients Suspected of Covid-19 - Pauzan, Pauzan; Kurniawan, Edy (Jurnal Biologi Tropis, 2024)
Severe acute respiratory syndrome corona virus 2 (SARSCOV-2) is a virus that causes corona virus desease (Covid-19), namely a respiratory sindrome desease that comes from the beta corona virus group. A serious problem with Sarscov-2 infection is when a cytokine storm appears which is produced as the body’s response to an inflammatory reaction, but the presence of interleukin (cytokine)-10 as an anti-inflammatory cytokine can suppress inflammatory reactions to avoid cytokine storms. The study's objective was to characterize IL-10 levels in people who may have Covid-19. The research method is to use an analytical survey with a retrospective design. Interleukin-10 levels were measured utilizing the ELISA (Enzime Linked Immunosorbant Assay) method. Result: The average level of IL-10 in SARSCOV-2 utilizing the Real Time Polymerase Chain Reaction (RT-PCR) method to detect positive Covid-19 suspect samples (83.16 pg/ml) was higher than SARSCOV-2 negative Covid-19 suspects (81.03 pg/ml). Conclusion: the comparison of IL-10 levels in positive Covid-19 suspects and negative Covid-19 suspects using the RT-PCR technique has an insignificant difference in levels because naturally Pro- and anti-inflammatory cytokines' reciprocal responses show that the immune response of the samples from suspected Covid-19 patients used is still very strong (IL-10).